Fire Hazard, Vulnerability, and Fire Protection Assessment in North Jakarta - Alfiansah Rahadian; Fatma Lestari; Debby Paramitasari (Health Notions, 2022)
Jakarta as the capital of Indonesia is progressing in the industrial and economic fields, facing problems in rapid population density and settlement. Dense population and housing in Jakarta increase the risk of fire. The objective of this study is to conduct hazard mapping, vulnerability, and fire protection assessment in Cilincing, Tanjung Priok, dan Penjaringan, North Jakarta. This study used cross-sectional method with non-probability sampling: stratified sampling. Data were collected using Fire Risk Assessment checklist, focus group discussion, and questionnaire. Instrument was developed using disaster Fire Risk approach including Fire Hazards, Vulnerability and Fire Protection / Fire Management. The instrument consists of Fire Risk Assessment Checklist for Local Government Fire Department and Questionnaire for Head of Neighborhood (Ketua RW). Data were then analyzed using descriptive analysis, bar chart and spider web diagram. The 15 areas of Cilincing, Tanjung Priok, dan Penjaringan were categorized at 9 medium risk and 6 high risk area. It is recommended to improve urban fire management, including provide additional city hydrants and ensure adequate and accessible city hydrant, and maintain regular program for hydrant inspection and testing. Fire Department also need to ensure proper fire protection in place for high-risk community activities, disseminate information regarding the use of building compartments with non-combustible materials, and educate residents about fire prevention and extinguishing, as well as community empowerment to be involved in fire emergency drill. Keywords: fire hazard; fire vulnerability; fire protection assessment